-(-(neg(

R

↳Dependency Pair Analysis

-'(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -'(-(x,y), -(x,y))

-'(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -'(x,y)

Furthermore,

R

↳DPs

→DP Problem 1

↳Polynomial Ordering

**-'(-(neg( x), neg(x)), -(neg(y), neg(y))) -> -'(x, y)**

-(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -(-(x,y), -(x,y))

The following dependency pair can be strictly oriented:

-'(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -'(x,y)

Additionally, the following usable rule w.r.t. to the implicit AFS can be oriented:

-(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -(-(x,y), -(x,y))

Used ordering: Polynomial ordering with Polynomial interpretation:

_{ }^{ }POL(-'(x)_{1}, x_{2})= x _{2}_{ }^{ }_{ }^{ }POL(neg(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(-(x)_{1}, x_{2})= 1 + x _{2}_{ }^{ }

resulting in one new DP problem.

R

↳DPs

→DP Problem 1

↳Polo

→DP Problem 2

↳Polynomial Ordering

**-'(-(neg( x), neg(x)), -(neg(y), neg(y))) -> -'(-(x, y), -(x, y))**

-(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -(-(x,y), -(x,y))

The following dependency pair can be strictly oriented:

-'(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -'(-(x,y), -(x,y))

Additionally, the following usable rule w.r.t. to the implicit AFS can be oriented:

-(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -(-(x,y), -(x,y))

Used ordering: Polynomial ordering with Polynomial interpretation:

_{ }^{ }POL(-'(x)_{1}, x_{2})= x _{2}_{ }^{ }_{ }^{ }POL(neg(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(-(x)_{1}, x_{2})= x _{2}_{ }^{ }

resulting in one new DP problem.

R

↳DPs

→DP Problem 1

↳Polo

→DP Problem 2

↳Polo

...

→DP Problem 3

↳Dependency Graph

-(-(neg(x), neg(x)), -(neg(y), neg(y))) -> -(-(x,y), -(x,y))

Using the Dependency Graph resulted in no new DP problems.

Duration:

0:00 minutes